Legal Protection for Winning Bidders in Mortgage-Right Execution Auctions - Zainudin Hasan; Kiki Dwi Susilowati (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2026)
Purpose: This study examines legal protection for good-faith winning bidders in mortgage-right execution auctions when land ownership disputes arise. It focuses on Decision Number 12/Pdt.Bth/2024/PN.Sdn to analyze how legal certainty in auction outcomes is tested when the winning bidder cannot immediately obtain physical possession of the auctioned land. Research Methodology: This study applies normative legal research using statutory, conceptual, and case approaches. The analysis draws on mortgage-right law, auction regulations, land registration rules, court decisions, legal doctrine, and supporting institutional information related to auction implementation. Results: The findings show that legal protection depends on three key elements: the validity of the auction procedure, the evidentiary strength of the Auction Minutes, and recognition of the bidder as a good-faith purchaser. In the analyzed case, the court protected the winning bidder because the auction was conducted through an authorized legal mechanism and the opposing party failed to prove a stronger ownership right. Conclusions: Indonesian auction law provides formal legal certainty for good-faith winning bidders. However, this certainty remains incomplete when the bidder faces resistance in obtaining physical control of the land.Limitations: This study is limited to one court decision and selected institutional information from the auction process. Contributions: This study highlights the gap between formal acquisition through auction and the practical realization of ownership through possession.